IN VITRO ACTIVATION OF EARLY-STAGE APOPTOSIS OF T LYMPHOCYTES BY TRANSFERRING APOPTOTIC AUTOLOGOUS CELL CULTURE COMPONENTS IN PATIENTS WITH RHEUMATOID ARTHRITIS - T. Ya. Abramova; V. A. Tsura; E. A. Blinova; A. Yu. Morenkova; V. A. Kozlov (Медицинская иммунология)
Defects in programmed death of peripheral blood lymphocytes may result into autotolerance and chronic persistence of inflammatory reaction in rheumatoid arthritis. According to recent data, apoptosis is not an autonomous process, i.e., an excessive accumulation of cells in conjunction with a depleted medium leads to cellular excess, thus causing effect of cells already committed to apoptosis upon surrounding cells, by morphogenetic damage due to mechanical forces. Such effects are called compensatory proliferation or apoptosis-induced proliferation. Extracellular vesicles (ectosomes and apoptotic bodies) also have a negative effect on cultured cells, triggering their programmed apoptotic death. In turn, apoptosis can also be controlled by neighboring cells in non-autonomous manner.We conducted studies that allowed us to optimize methods aimed at the initiation of apoptotic cell death and to investigate the effects of apoptotic environment upon autologous cells under physiological conditions. The selected conditions in combination with a fluorescent labeling of lymphocytes and subsequent separate flow cytometric analysis allowed us to evaluate parameters of early apoptosis in subpopulations of peripheral blood T-lymphocytes in rheumatoid arthritis. In vitro studies of cells from the patients with rheumatoid arthritis allowed us to reveal a pronounced readiness of primary (CFSE) and secondary (CFSE+)-induced T lymphocytes for early apoptosis after stimulation with anti-CD3 antibodies. It was observed both against initial level of apoptosis, and when compared to cells induced for apoptosis. The obtained data suggest that stimulation of T lymphocytes with antibodies against CD3, and, as a result, an in vitro rise in cell proliferation rate leading to increased levels of early apoptosis not only among the cells directly receiving a proliferative stimulus, but also to increased effect of cellular and humoral components from anti-CD3-stimulated cultures upon normally proliferating lymphocytes.The transfer of an autologous apoptotic “aCD3” and dexamethasone-stimulated cultures, which were initially induced under conditions of cell overcrowding and medium exhaustion, was shown to activate the process of early apoptosis among normally proliferating cells. Glucocorticoids are known to serve as agents of cell death induced by activation. At pharmacological concentrations, glucocorticoids and their synthetic analogues stimulate endonucleases in activated lymphocytes. These enzymes destroy DNA in the internucleosomal regions thus resulting into cell apoptosis. The results obtained in present study suggest an opportunity of an in vitro early-stage apoptosis induction in T lymphocytes from the patients with rheumatoid arthritis, by means of cells subjected to activation-induced apoptosis.